Analisis Pendapatan dan Kelayakan Usahatani Padi Sawah di Desa Umbu Pabal Kecamatan Umbu Ratu Nggay Barat Kabupaten Sumba Tengah - Aristo Dapa Ole; Elsa Christin Saragih (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
The purpose of this study was to analyze the income and feasibility of lowland rice farming. The study was conducted in Umbu Pabal Village, Umbu Ratu Nggay Barat District, Central Sumba Regency from May to June 2025. The research sample was 81 lowland rice farmers in Umbu Pabal Village. Data analysis used in this study includes income analysis and feasibility analysis of lowland rice farming. The results of the income analysis show that the average income of lowland rice farming in Umbu Pabal Village is IDR 31,548,817.37 per hectare. The results of the feasibility analysis of lowland rice farming in Umbu Pabal Village indicate that agricultural activities are feasible to implement.